Guided Inquiry and Simple Science KIT Media: Their Implications for Students' Science Process Skills - Syafrilianto, Syafrilianto; Taufiq, Muhammad Aries; Putri, Rahmi Eka; Rasydin, Ahmad (Journal of Natural Science and Integration, 2024)
The purpose of this study was to examine how the guided inquiry model affected the science process abilities of university students who studied the basic concept of elementary school-level science. This study utilized a type of quasi-experimental research approach called a one group pretest-posttest design to examine the effect of treatment administered to one group before and after the treatment by a test of science process skills questions. Out of the 182 students enrolled in the Madrasah Ibtidaiyah Teacher Education Study Program at IAIN Padangsidimpuan, 25 students from the fourth semester of 2022 served as the study's samples. Using a paired sample t-test and the SPSS 22.0 program, the study's findings showed that there was a difference in the science process skill scores of the students between the pre- and post-test results. It was discovered that the paired sample t-test had a significance value of 0.168, which was higher than 0.05. In conclusion, the guided inquiry model assisted with simple scientific KIT media was found to have a significant effect on the science process skill scores of students at PGMI IAIN Padangsidimpuan, especially about temperature and heat materials.  Keywords: guided inquiry, science process skills, simple science media kit